The Strategy of Khairuddin Gondanglegi Vocational High School in Creating an Effective Learning Culture for Islamic Education Subjects - Moh. Thoha Habibulloh; Aries Musnandar (Journal of Noesantara Islamic Studies, 2024)
The research in this thesis is motivated by the uniqueness in which teachers at SMK Khairuddin Gondanglegi carry out their roles well. Teachers are able to use technology in learning. The infrastructure of SMK Khairuddin Gondanglegi is met the needs of students and teachers. This school is a vocational school that requires more infrastructure to support learning. The school has fulfilled with a laboratory for each department in the school. School efforts in realizing the best graduates, the school has its own strategy in creating an effective learning culture. Based on the above context, the objectives of this study are to: (1) describe the strategy of Khairuddin Gondanglegi Vocational High School in creating an effective learning culture for Islamic Religious Education subjects, (2) What are the supporting and inhibiting factors of Khairuddin Gondanglegi Vocational High School in creating an effective learning culture for Education subjects Islam. The study uses a qualitative research method with a case study approach and the collection procedures used, namely participant observation, in-depth interviews and documentation. The results of the study indicate that the strategy implementation with the right steps by paying attention to the supporting and inhibiting factors can create an effective learning culture in as expected. The supporting and inhibiting factors for creating an effective learning culture involve the individual himself, the school, the family, and the community. In order to create an effective learning culture, it is necessary to have good cooperation between the individual himself, the school, the family, and the community.